A finite horizon EPQ model for deteriorating items with shortages under permissible delay in payments. (15th November 2010) - Valliathal, M.; Uthayakumar, R.
This paper discusses a deterministic finite horizon economic production lot size (EPLS) model for deteriorating items under permissible delay in payments. Shortages are allowed and backlogged partially. Three models are developed over a finite planning horizon. The existence and uniqueness of the optimal solutions of the proposed models are examined. Here, production cycle time, the time at which the shortage begins, production stopping time, shortage ending time and total number of production cycles are taken as decision variables. Numerical examples are given to illustrate the model.